High-value crops help Central Asia revitalize agriculture sector - Akramov, Kamiljon T.; Chen, Kevin Z.; Central Asia Regional Economic Cooperation Institute (Asian Development Bank, 2020)
CAREC countries adopt diversification strategies as they shift to a market-oriented agriculture.